The Ethics of Artificial Intelligence in Pathology and Laboratory Medicine: Principles and Practice - Brian R. Jackson MD, MS; Ye Ye PhD; James M. Crawford MD, PhD; Michael J. Becich MD, PhD; Somak Roy MD; Jeffrey R. Botkin MD; Monica E. de Baca MD; Liron Pantanowitz MD, MHA (Elsevier, 2021)
Growing numbers of artificial intelligence applications are being developed and applied to pathology and laboratory medicine. These technologies introduce risks and benefits that must be assessed and managed through the lens of ethics. This article describes how long-standing principles of medical and scientific ethics can be applied to artificial intelligence using examples from pathology and laboratory medicine.